Trade-Off Between Triadimefon Sensitivity and Pathogenicity in a Selfed Sexual Population of Puccinia striiformis f. sp. Tritici - Tian, Yuan; Meng, Yan; Zhao, Xiaocen; Chen, Xianming; Ma, Hengbo; Xu, Sanding; Huang, Lili; Kang, Zhensheng; Zhan, Gangming (Frontiers in Microbiology, 2019)
Stripe rust, caused by Puccinia striiformis f. sp. tritici (Pst), is one of the most destructive diseases of wheat and has been largely managed using demethylation inhibitor (DMI) fungicide triadimefon in China. To determine the sensitivity of Pst, a Chinese Pst isolate and its sexually produced progeny isolates were tested with triadimefon using the detached leaf method. The half maximal effective concentration (EC50) values varied greatly among the progeny isolates, ranging from 0.06 mg L-1 to 7.89 mg L-1. Twenty-six of the 56 tested progeny isolates were less sensitive to triadimefon than the parental isolate. A single-nucleotide mutation at the 401 position resulting in an amino acid change from tyrosine (Y) to phenylalanine (F) in the 134th codon (Y134F) of CYP51, the target gene of DMI fungicide, was identified in the parental isolate. The 87 tested progeny isolates segregated into 19 homozygous wild type (AA), 40 heterozygous (AT), and 28 homozygous mutant (TT) genotypes, fitting a 1:2:1 ratio (χ2 = 2.43; P = 0.30). The mutant isolates had higher EC50 values than the wild type isolates. Significant differences in logEC50 were found between the mutant isolates and the wild type isolates (P = 2.2e-16). However, homozygous and heterozygous mutant isolates were not significantly different (P = 0.21), indicating dominant mutation. Twenty-two progeny isolates were used to inoculate a susceptible wheat variety, and latency period and lesion growth were recorded to compare wild type and mutant isolates for the pathogenicity fitness components. A moderate but significant negative correlation was detected between lesion growth and sensitivity to triadimefon (r = -0.53; P = 0.01). No significant variation in lesion growth was found between homozygous and heterozygous mutant isolates (P = 0.83). In the case of latency period and triadimefon sensitivity, no significant correlation was found (P = 0.17). These results are useful for understanding reduced sensitivity in the pathogen population and improving stripe rust management.